Classification and some properties of triptans - Antal, Irуna (СНУ, 2013)
Triptans are a group of tryptamine-based drugs used in the acute treatment of migraine headaches. Structurally related to the neurotransmitter serotonin, triptans acts by selectively binding to serotonin type-1D receptors. The present paper submitted the classification and some properties of triptans (almotriptan, eletriptan, frovatriptan, naratriptan, sumatriptan, rizatriptan, zolmitriptan).
Keywords: Triptans; Classification; Properties